A Convenient route for the synthesis of antimicrobial 1, 3, 4- thiadiazole derivatives - Mishra, AD (BIBECHANA, 2012)
Thiosemicarbazide of 6-chloro-2- aminobenzothiazole on cyclization with different aromatic carboxylic acids in Phosphorus oxychloride provided the corresponding 2-aryl-5-(6’-chloro-1’,3’-benzothiazole-2-yl-amino)-1,3,4-thiadiazoles 4a-j. The compounds are characterized by elemental analysis, IR and 1H NMR spectral data. All the compounds are evaluated in vitro for their antimicrobial activities against several fungal and bacterial strains and showed significant activities. Keywords: Aminobenzothiazole; 1, 3, 4- thiadiazole; antimicrobial; cyclization DOI: http://dx.doi.org/10.3126/bibechana.v8i0.4766 BIBECHANA 8 (2012) 17-22